Recent advances in the treatment of type 2 diabetes mellitus with obesity - S. V. Yargin (Лечащий Врач)
The drugs contributing to weight loss are preferable For treatment of type 2 diabetes mellitus with overweight. Along with the widely used metformin, the following medication classes are discussed. The GLP-1 receptor agonists stimulate insulin secretion, slow down the gastric emptying, contributing to weight loss. The SGLT-2 inhibitors lessen the renal glucose reabsorption, reduce the blood pressure and contribute to a body weight reduction. A similar effect on the body weight should be awaited from an inhibitor of intestinal alpha-glucosidase (acarbose); however, its efficiency depends on the carbohydrate content of the food.